Antisense Oligonucleotides against miR-21 Inhibit the Growth and Metastasis of Colorectal Carcinoma via the DUSP8 Pathway - Tao Ding; Panpan Cui; Ya Zhou; Chao Chen; Juanjuan Zhao; Hairong Wang; Mengmeng Guo; Zhixu He; Lin Xu (Elsevier, 2018)
Accumulating research has documented that microRNA-21 (miR-21) plays an important role in the development of human colorectal carcinoma (CRC). Our recent work also showed that antisense oligonucleotides (ASOs) against miR-21 can impair the growth of CRC cells in vitro. However, the potential role of miR-21 in gene therapy against CRC remains to be fully elucidated. Here, we further observed the effect of ASOs against miR-21 on the growth and metastasis of CRC in vivo using a xenograft model of human CRC. We found that ASOs could effectively inhibit the growth and metastasis of CRC in vivo, accompanied by downregulated expression of miR-21 and reduced transduction of the AKT and ERK pathway. Mechanically, global gene expression analysis showed that the expression of DUSP8, a novel target of miR-21, was upregulated in tumor mass. Furthermore, overexpression of DUSP8 could remarkably suppress the proliferation and migration of CRC cells in vitro. Finally, downregulation of DUSP8 could abrogate the effects of ASOs against miR-21 on the proliferation and migration of CRC cells, as well as altered transduction of the AKT and ERK signaling pathway. Together, these data suggest that ASOs against miRNAs are an attractive and potential therapeutic for the treatment of human CRC and warrant further development. Keywords: miR-21, ASOs, colorectal carcinoma, growth, DUSP8